Emerging acts of violence: neologisms of crime - Cañete-González, Paola (2023)
In recent years, factors of change such as the evolution of society or technology have contributed to the creation of new words in various areas, such as crime. The aim of this study is to examine the neological productivity in this area and to identify the linguistic resources used to create these new lexemes. This can be seen in the press, which is an ideal medium for the study of neologisms, because it addresses current affairs and contingencies and facilitates the introduction of new words in the language. For this reason, five Chilean newspapers from 2020 and 2021 in their digital edition were selected, lexical units related to crime were compiled according to the psycholinguistic and lexicographical criteria and were then classified in six categories. Subsequently, the employed linguistic mechanisms and the most frequent word formation processes were analyzed to shed light on new criminal practices in society and how the language makes them visible through the creation of new words. The results revealed a tendency to create syntagms based on existing crimes (secuestro extorsivo), use of suffixes (portonazo), compounding (cibersabotaje) and semantic change (vaquero). It was confirmed that the vocabulary is an inexhaustible source for the creation of new words that allows members of a community to express new realities and social dynamics.